Fiction and Tolerance: Comparative Perspectives from Kuwaiti and Indonesian Literature - Syah, Ahfa Rahman (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
In preserving diversity, literature frequently plays a central role by foregrounding themes and ideologies of tolerance. The issue of tolerance has become a global concern in literary studies, ranging from the Arab world to Indonesia. One Arab novel that explores this theme is Fi’rān Ummī Hiṣṣah (2015) by Su‘ud al-San‘usi from Kuwait, which narrates sectarian conflict between Sunni and Shi‘ite communities. In the Indonesian context, Kambing dan Hujan (2015) by Mahfud Ikhwan highlights encounters and tensions between Nahdlatul Ulama (NU) and Muhammadiyah. This study aims to analyze the representation of tolerance in both novels and compare their approaches. The research employs a qualitative method with content analysis techniques. Data were collected through close reading of characters’ actions, dialogues, and narrative events in both works. The theoretical framework is grounded in Abu A‘la Maududi’s theory of tolerance, Melani Budianta’s concept of Literature and Cross-Cultural Interaction, Ian Watt’s sociology of literature, and Henry H. Remak’s comparative literature. The findings reveal that both novels position tolerance as a solution to intra-religious conflicts. Although they share the same objective-preserving religious diversity-each novel presents distinct forms of tolerance shaped by its socio-cultural context. Fi’rān Ummī Hiṣṣah represents tolerance through events infused with communal interaction and everyday coexistence in public spaces, such as the exchange of educational institutions, attending funerals and mourning ceremonies, accepting ritual differences, and sharing public domains. Meanwhile, in Kambing dan Hujan, tolerance appears through ritual compromise, doctrinal negotiation, and religious dialectics, as each group is given equitable space to articulate its interpretations, arguments, and theological perspectives. These differences stem from the fact that Kuwait remains relatively distant from an institutionalized tradition of tolerance; thus, the novel presents inspirational forms of tolerance manifested through social practices of coexistence. In contrast, Indonesia-long accustomed to “Bhinneka Tunggal Ika” (Unity in Diversity) and diverse religious traditions offers a more intimate form of tolerance through dialogical engagements with doctrines, rituals, interpretations, and collective meaning-making among groups. Ultimately, both novels demonstrate that tolerance does not eliminate differences but rather reflects the willingness to manage and negotiate them constructively.